KONFLIK SOSIAL DALAM NOVEL BAYANG SURAM PELANGI KARYA ARAFAT NUR - Paulia, Sindi; Sutejo, Sutejo; Astuti, Cutiana Windri (STKIP PGRI Ponorogo Press, 2022)
This research is aimed at describing the forms, causing factors, and the impacts of social conflicts in novel Bayang Suram Pelangi by Arafat Nur. Social conflict is one of the conflicts that occur due to social contact between humans. This research is descriptive qualitative study. In this study, the data was obtained by reading carefully and then note taking. The data are analyzed through the following steps; data reduction, data presentation and drawing conclusion. The results of this study indicate that there are three forms of social conflict, they are (1) personal conflict, (2) conflict between social classes, and (3) political conflict. Based on the analysis, the researchers identified two factors that cause social conflicts; they are individual differences and the different interests. Further, the impacts caused by the social conflicts within the novel are; (1) the increasing of in-group solidarity, (2) personality changes, (3) the destruction of property and the loss of life.